Correlación de la formación moral y educación ambiental de los estudiantes del primer grado “B” de educación secundaria de la Institución Educativa Particular Simón Bolívar de Tarapoto - Ramirez Rodas, Carlos Alberto (2008)
The present investigation has allowed us to meditate on the importance of the Correlation of the Moral Formation and Environmental Education in the integral development of the students, making possible its development, its fullness and its happiness. The environmental education cannot understand it if it is not in a parallel and simultaneous way with that that traditionally know as moral formation. Difficultly an educating will take care of the environment if he/she doesn't take care to itself, difficultly it will respect the environment but it is respected itself and the other ones. It is clear that the education in the XXI century must base on the following pillars: Learn how to KNOW, Learn how to MAKE, Learn how to LIVE, Learn how to BE. The study consists of four chapters; in the first chapter the position of the problem is developed: lack of moral formation in the environmental topic of the students of the secondary level of the Educational Institution Simon Bolivar, that which allows us to determine the correlation degree that exists between the Moral Formation and the Environmental Education. In the second chapter we develop the theoretical mark - conceptual, observing the antecedents modernized on moral formation, we revise in systematic form the pertinent literature, o give a context appropriately our investigation. In the third chapter we develop the methodological aspects of the investigation, developing sorne results of our investigation diagnosis of Correlation of the Moral Formation and Environmental Education partially, in the Particular Educational Institution Simon Bolívar. In first term we analyze fundamental results, second moment, the information facto - perceptible remaining it is presented like I annex. In the fourth chapter we present our obtained results that they confirm the investigation hypothesis, conclusions and recommendations. Finally the bibliographical references, at the same time that they express the learned contribution of our investigation they offer solidity to the investigation testifying the presence of a scientific base in the elaboration of the work.